Helping stakeholders select and apply appraisal tools to mitigate soil threats: Researchers' experiences from across Europe. (1st March 2020) - Okpara, Uche T.; Fleskens, Luuk; Stringer, Lindsay C.; Hessel, Rudi; Bachmann, Felicitas; Daliakopoulos, Ioannis; Berglund, Kerstin; Blanco Velazquez, Francisco Jose; Ferro, Nicola Dal; Keizer, Jacob; Kohnova, Silvia; Lemann, Tatenda; et al.
Abstract: Soil improvement measures need to be ecologically credible, socially acceptable and economically affordable if they are to enter widespread use. However, in real world decision contexts not all measures can sufficiently meet these criteria. As such, developing, selecting and using appropriate tools to support more systematic appraisal of soil improvement measures in different decision-making contexts represents an important challenge. Tools differ in their aims, ranging from those focused on appraising issues of cost-effectiveness, wider ecosystem services impacts and adoption barriers/opportunities, to those seeking to foster participatory engagement and social learning. Despite the growing complexity of the decision-support tool landscape, comprehensive guidance for selecting tools that are best suited to appraise soil improvement measures, as well as those well-adapted to enable participatory deployment, has generally been lacking. We address this gap using the experience and survey data from an EU-funded project (RECARE: Preventing and REmediating degradation of soils in Europe through land CARE ). RECARE applied different socio-cultural, biophysical and monetary appraisal tools to assess the costs, benefits and adoption of soil improvement measures across Europe. We focused on these appraisal tools and evaluated their performance against three broad attributes that gauge their differences and suitability for widespread deployment to aid stakeholder decision making in soil management. Data were collected using an online questionnaire administered to RECARE researchers. Although some tools worked better than others across case studies, the information collated was used to provide guiding strategies for choosing appropriate tools, considering resources and data availability, characterisation of uncertainty, and the purpose for which a specific soil improvement measure is being developed or promoted. This paper provides insights to others working in practical soil improvement contexts as to why getting the tools right matters. It demonstrates how use of the right tools can add value to decision-making in ameliorating soil threats, supporting the sustainable management of the services that our soil ecosystems provide. Highlights: We propose guidelines for selecting tools for appraising soil improvement measures. Tools designed with stakeholders' needs in mind are capable of fostering local buy-in. Ensemble of tools facilitates understanding of how remediation options work best. Researchers support sequencing of tools in evaluating benefits of remediation options.